Heterophase Boundary for Active Hydrogen Evolution in MoTe2. (1st December 2021) - Lee, Yongjoon; Ling, Ning; Kim, Dohyun; Zhao, Mali; Eshete, Yonas Assefa; Kim, Eunah; Cho, Suyeon; Yang, Heejun
Abstract: The phase engineering of transition metal dichalcogenides (TMDs) is considered a promising strategy for promoting efficient catalysis, such as the hydrogen evolution reaction (HER). While theoretical studies predict the presence of catalytically active atomic sites at heterophase boundaries in TMDs, conventional bulk HER measurements are not able to precisely explore these 1D heterophase regions for HER. Here, one reports on active HER occurring at heterophase boundaries between the semiconducting 2H and metallic 1T' phases in large‐scale MoTe2 grown via chemical vapor deposition. Microreactors are used to investigate the local HER at varying lengths of 1D heterophase boundaries, and the results are systematically compared with the HER performance at the pristine basal planes of MoTe2 . Despite the small area ratio between the 1D heterophase boundary and the open region for local HER, a clear improvement in HER is observed with a turnover frequency of 317 s –1 . The Kelvin probe force microscopy determines a surface potential difference of 50 mV across the heterophase boundary, which supports sharp band bending and local charge accumulation as the basis for the TMDs' efficient electrochemical catalysis. Abstract : Active hydrogen evolution reaction (HER) at heterophase boundaries between semiconducting 2H and metallic 1T' phases in large‐scale MoTe2 is reported. Despite the small area ratio of the 1D heterophase boundary to the basal plane, HER is improved up to a turnover frequency of 317 s −1 at the 1D geometry. Kelvin probe force microscopy demonstrates a sharp band bending for the HER.